Freedom and opportunity. Distributive justice considerations in amartya sen and philippe van parijs (2021)
The purpose of this essay is to approach the conceptions of distributive justice in two contemporary economists: Amartya Sen and Philippe Van Parijs. To this end, the notion of capabilities that Martha Nussbaum presents in her book “the limits of justice” is addressed transversally. This approach allows us to trace a common thread for understanding Sen and Van Parijs’ conceptions of freedom and justice. From these conceptual approaches, it will be argued that, in all cases, material conditions are indispensable for the exercise of human freedom. © 2021, Universidad del Zulia. All rights reserved.